1-Kestose consumption during pregnancy and lactation increases the levels of IgA in the milk of lactating mice. Issue 5 (4th May 2014) - Jinno, Shinji; Nakamura, Yoshitaka; Nagata, Masashi; Takahashi, Takeshi
Abstract: To examine the effect of dietary supplementation with 1-kestose on the IgA levels in milk, BALB/c mice were fed diets with or without 5% 1-kestose during pregnancy and lactation. The total and specific IgA levels in the milk were measured at 7 and 14 days after delivery. A two-way ANOVA with repeated measures resulted in a significant effect of 1-kestose-supplementation on total IgA concentrations ( p < 0.05) and the level of anti- Bacteroides IgA ( p < 0.05). A significant positive correlation was found between the mean count of Bacteroides spp. in maternal feces and the total IgA concentration in maternal milk ( r = 0.55, p < 0.05), suggesting a potential link between the gut and mammary gland immune system. In conclusion, this study demonstrated the effects of dietary prebiotics on milk IgA production. Graphical abstract: : Consumption of 1-kestose, a major component of fructooligosaccharides, by pregnant and lactating mice increased the total IgA concentration in the mouse milk.